2022
DOI: 10.1097/md.0000000000031046
|View full text |Cite
|
Sign up to set email alerts
|

Impaired rate-dependent depression of the H-reflex in type-2 diabetes, prediabetes, overweight and obesity: A cross-sectional study

Abstract: Type-2 diabetes is a chronic metabolic disorder characterized by hyperglycemia, resulting from deficits in insulin secretion or insulin resistance. According to the International Diabetes Federation, approximately 463 million people suffered from this condition in 2019, with a rapidly increasing impact in low-and middle-income countries. Obesity is a well-known risk factor for diabetes, and current data project a continuous increase in diabetes prevalence worldwide in obese individuals. Among the common compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Overall, our results confirm previous findings indicating that GVS increases the excitability at the neural elements involved in the H-reflex ( Lowrey and Bent, 2009 ; Okada et al, 2018 ; Nakamura et al, 2021 ); however, this increase in excitability did not affect the P-AD in healthy individuals, suggesting preservation of inhibitory spinal mechanisms. In this context, it has been described that a reduction or loss of the P-AD in pathological conditions occurs, such as in multiple sclerosis ( Cantrell et al, 2022 ), spinal cord injury ( Nielsen et al, 1995 ; Knikou and Murray, 2019 ), and recently, in diabetic neuropathy ( Lee-Kubli and Calcutt, 2014 ; Marshall et al, 2017 ; Worthington et al, 2021 ) and prediabetic, overweight and obese subjects ( Salinas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results confirm previous findings indicating that GVS increases the excitability at the neural elements involved in the H-reflex ( Lowrey and Bent, 2009 ; Okada et al, 2018 ; Nakamura et al, 2021 ); however, this increase in excitability did not affect the P-AD in healthy individuals, suggesting preservation of inhibitory spinal mechanisms. In this context, it has been described that a reduction or loss of the P-AD in pathological conditions occurs, such as in multiple sclerosis ( Cantrell et al, 2022 ), spinal cord injury ( Nielsen et al, 1995 ; Knikou and Murray, 2019 ), and recently, in diabetic neuropathy ( Lee-Kubli and Calcutt, 2014 ; Marshall et al, 2017 ; Worthington et al, 2021 ) and prediabetic, overweight and obese subjects ( Salinas et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salinas et al. ( 29 ), reported that the T2DM group presented a significantly increased latency compared to the control group (p < 0.001), and when subgroups were analyzed for p-DPN and p+DPN, latencies were significantly prolonged in the non-painful group at all stimulation frequencies. Also, Marshall et al.…”
Section: Alterations Of the H-reflex And H-reflex Rate-dependent Depr...mentioning
confidence: 94%
“…In the same study, it is reported an improvement of 7.5% in the RDD after 2 weeks of gabapentin treatment ( 34 ). Nevertheless, Salinas et al., reported that although there is greater impairment of RDD in subjects with painful neuropathy, RDD is also impaired in subjects with non-painful diabetic neuropathy and they did not find enhanced RDD in any subpopulation of T2DM subjects ( 29 ). A common observation between both research groups is that H-reflex might be absent or severely attenuated in some patients, specifically in those with severe DSPN, so this test may not be suitable for all subjects, being limited to mild and moderate neuropathy ( 26 , 29 , 31 ).…”
Section: Alterations Of the H-reflex And H-reflex Rate-dependent Depr...mentioning
confidence: 98%
See 2 more Smart Citations